Epidemiology of human respiratory tract infection in Chongqing, China after COVID-19–based on surveillance data encompassing 17 respiratory pathogens - Li, Tingting; Long, Jiang; Li, Zhourong; Xiong, Yu; Feng, Luzhao; Jiang, Mingyue; Sun, Yanxia; Qi, Li (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundRespiratory tract infections (RTIs) are an important public health concern, and SARS-CoV-2 affects the epidemic pattern of RTIs globally. National multipathogenic surveillance for RTIs was conducted in mid-October 2023. However, baseline data on the pathogen spectrum of RTIs in Chongqing, China, before mid-October 2023 are limited.MethodsA descriptive analysis was conducted to determine the epidemiology of RTIs in Chongqing, China, in 2023.Results A total of 1,894 individuals were included in 2023, with an overall positivity rate of 28.7%. The highest overall positivity rate was observed in May 2023 (53.0%). Different predominant respiratory pathogens were observed among different age groups. Among all single-infected individuals, SARS-CoV-2 accounted for 32.1%, followed by IFV, which accounted for 28.2%. In the children group, RSV ranked first, accounting for 15.7%. Among school-aged children, IFV ranked the top, accounting for 46.7%. SARS-CoV-2 ranked the top among adults and the elderly, accounting for 45.5% and 47.0%, respectively.ConclusionsThe local pathogen spectrum of RTIs one year after the onset of COVID-19 showed that SARS-CoV-2 was steady, and viral infection might be the main cause of RTIs. Both upper respiratory tract infections and lower respiratory tract infections (LRIs) showed high RTI positivity rates. The pathogen spectra of upper respiratory tract infections (URIs) and LRIs differ in adults. Holistic surveillance of RTIs is necessary to estimate the local disease burden. Vaccination against respiratory infections remains an important strategy to prevent and control RTIs.